Investigating pair distribution function use in analysis of nanocrystalline hydroxyapatite and carbonate-substituted hydroxyapatite - Arnold, Emily; Keeble, Dean S.; Evans, J. Paul O.; Greenwood, Charlene; Rogers, Keith (International Union of Crystallography, 2022)
Hydroxyapatite (HA) is a complex material, which is often nanocrystalline when found within a biological setting. This work has directly compared the structural characteristics derived from data collected using a conventional laboratory-based X-ray diffractometer with those collected from a dedicated pair distribution function (PDF) beamline at Diamond Light Source. In particular, the application of PDF analysis methods to carbonated HA is evaluated. 20 synthetic samples were measured using both X-ray diffraction (XRD) and PDFs. Both Rietveld refinement (of laboratory XRD data) and real-space refinement (of PDF data) were used to analyse all samples. The results of Rietveld and real-space refinements were compared to evaluate their application to crystalline and nanocrystalline hydroxyapatite. Significant relationships were observed between real-space refinement parameters and increasing carbonate substitution. Understanding the local order of synthetic hydroxyapatite can benefit several fields, including both biomedical and clinical settings.
Keywords: powder diffraction; bone mineral; carbonate-substituted hydroxyapatite; X-ray diffraction; total scattering; pair distribution function